Epidemiologie des Handekzems in Deutschland - Ofenloch, Robert; Weisshaar, Elke (Der Hautarzt, 2019)
Background: There is a lack of epidemiological data describing patterns of hand eczema with reference to the general German population.ObjectiveEpidemiological data were extracted from all internationally published clinical studies which investigated hand eczema in Germany. Material and methods: A search was carried out for all clinical studies performed in Germany in the previous 10 years involving hand eczema patients. Inclusion criteria were that at least one author was listed with a German affiliation, that the study included original data and was published in an international journal with peer review. Results: This review included 39 studies, which were performed based on 29 original data sets. The median proportion of women was 53.7% and the median age 45.1 years. The 1‑year prevalence of hand eczema varied depending on the sample and type of data collection from 0.24% to 9.2%. The lifetime prevalence was estimated to be 2.6-16.0% and the point prevalence in dermatological practice was 6.7 %. In studies assessing the impact of hand eczema in specific occupations, women were underrepresented, large studies were carried out for metal workers but only a few small studies for nursing personnel. Conclusion: There is a lack of knowledge concerning the epidemiology of hand eczema in the general German population. While international studies found the first occurrence of hand eczema to be between the ages of 26 and 28 years, the mean age of patients seen in private dermatological practice in Germany was 20 years higher. These findings suggest that patients do not consult a dermatologist when hand eczema first appears, which can lead to a more severe course of the disease.